PENGGUNAAN MODEL WORDSQUARE DALAM MENINGKATKAN HASILBELAJAR PKN KELAS IV - Ramadhan, Ivan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem of research is whether there is an increase in student learning outcomes with the use of Wordsquare model in Class IV State Elementary School 12 Pontianak City. Research aims to improve learning outcomes through the wordsquare model.The method used in this research is descriptive method in the form of Classroom Action Research, is collaborative. Data collection techniques used are the technique of direct observation and measurement by means of data collection is the Student Worksheet. Setting research with subject Teachers / Researchers and students of class IV amounted to 37 students.The results of the three cycles obtained are: 1) The ability of the teacher to plan the learning model wordsquare experienced an average increase of 0.30 with an average value of 3.7. 2) The ability of teachers to implement learning model wordsquare experienced an average increase of 0.33 with an average value of 3.63. 3) Student learning result of wordsquare model has increased the cycles 13.89 with average value 66.12.Conclusion: using wordsquare model in Civic Education learning can improve student learning outcomes.Keywords: Learning outcomes, wordsquare models, Citizenship Education.